Sustainable Development and Green Economy: The Analysis of the Dynamics of the Energy Structure from Renewable Energies in Romania Through the Markov Chains Method - PÎRVU, Ramona; BOȚOTEANU (RĂDĂCINĂ), Geanina Iulia; ȚENEA, Lili (Journal of Advanced Studies in Finance; Vol 12 No 1 (2021): JASF Volume XII Issue 1(23) Summer 2021, 2021)
The climate changes increase the existing risks and generate new types of risks both for the natural systems and, directly or indirectly for the humanity. For the people from the vulnerable communities, the risks are higher, irrespective of the development degree. The communities from the rural environments are affected by the risks of the climate changes due to the need of relocating the agricultural activities in other less favorable places. The green economy is considered the main means through which sustainable development can be attained, taking not account the ecologic limits of the planet. On a national level, the most representative branch of the green economy is represented by the energy production sector from renewable energy. There is a total number of 639 of companies within this industry which exploit the four types of resources offered by our country to produce electric energy. T The article is structured on three parts: therefore, in the first part we did a research of the reference literature on the concepts of sustainable development and the green economy, in the second part we analyzed the renewable resources used for the energy production in Romania and the structure of the energy from renewable energies, in the period 2010 – 2020, studying at the end of the paper the dynamics of the energy structure from renewable resources with the help of the Markov chains method.